‘YorMeme’ for the girl, boy, bakla, tomboy plus a discourse analysis of Vice Ganda’s commentaries during the 2020–2024 Duterte-Marcos era - Pacinos, Matthew Aaron N.; Sánchez, Louie Jon A. (Quezon City University of the Philippines, Diliman, 2025)
As the present media landscape navigates various socio-political issues, the representation of the Lesbian, Gay, Bisexual, Transgender, Queer, Intersex, Asexual (LGBTQIA+) community remains to be challenged both by the current political climate and the Philippines’ religious-cultural setting. Conveniently, such a representation finds strength through the persona of the openly gay and unkabogable Vice Ganda who is at the forefront of the LGBTQIA+ discourse as one of the country’s contemporary celebrity superstars. However, existing studies limit Vice Ganda’s influence on issues related to gender, queer visibility, and comedy, thereby failing to establish the symbolic power of Vice Ganda and its potential to transcend to the political realm.

As Vice Ganda actively engages in discourses on different socio-political themes, the study aims to explore the political influence of his commentaries across the broadcast, digital, and emerging media texts he is involved with during the 2020 to 2024 Duterte-Marcos era. The inquiry includes tracing the trajectory of his career alongside socio-political movements and the discourses of his media texts. Following a qualitative research design, the study selected six key issues from 2020 to 2024. Each issue has one specific media text of Vice Ganda serving as the specific object of the study, including the discourse found from the audiences’ engagements. Through Maxwell McCombs and Donald Shaw’s Agenda-Setting Theory, Pierre Bourdieu’s Theory of Capital, and Judith Butler’s Theory of Performativity serving as the study’s frameworks, the study must be able to explicate the political themes of Vice Ganda’s commentaries, the impact of his texts, and the surrounding audience discourse. These frameworks aim to establish how Vice Ganda’s commentaries uphold political themes laced with a nuanced version of his comedy, allowing him to impact the Philippine political landscape and the audience discourse surrounding it
Thesis
Keywords: Gender identity -- Philippines; Gay men -- Philippines -- Social aspects